(untitled) (IITM Journal of Business Studies, 2024)
In recent years, the global financial landscape has undergone a significant transformation propelled by the rapid proliferation of Financial Technology (Fintech). This technological revolution has not only reshaped traditional financial services but has also democratized access to financial products and services, ushering in a new era of financial inclusion and empowerment. Understanding the underlying demographic dynamics behind Fintech adoption has become increasingly crucial for policymakers, financial institutions, and market participants alike, especially within emerging economies. This research aims to delve into the intricate interplay between demographic factors and Fintech adoption within the context of emerging economies. Through a multidimensional approach encompassing quantitative analysis and theoretical frameworks, the study endeavors to investigate the patterns and preferences across different demographic segments. By analyzing data from 15 emerging countries representing diverse regions across the globe, the research seeks to uncover insights into the drivers and barriers influencing Fintech adoption.